medical devices
By loading ligand-degradable polymers on the surface of iron-based medical devices, the coordination groups react with metal matrix corrosion products to form water-soluble coordination compounds, which solves the difficulty of absorbing corrosion products and metal ion toxicity of iron-based medical devices in the body. Problems, faster absorption and degradation are achieved, and biocompatibility is improved.
Patent Information
- Application Number
- CN202211475122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-02-13
- Filing Date
- 2017-12-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2037-12-28
AI Technical Summary
The solid corrosion products generated by corrosion in the body of existing iron-based medical devices are difficult to absorb and metabolize, and the high concentration of metal ions may lead to cytotoxicity. The existing ligand complexing agent has low solubility and is difficult to load on the surface of the device, which limits its Application effect.
Degradable polymer reacts with ligands to form coordination groups to form ligand-degradable polymers. Coordinate groups react with corrosion products of corrosive metal matrix under physiological environment to form water-soluble coordination Compounds, reduce metal ion concentration and accelerate absorption of corrosion products.
By generating water-soluble coordination compounds, the risk of cytotoxicity of metal ions is reduced, the absorption cycle is shortened, and the biocompatibility and rehabilitation efficiency of iron-based medical devices are improved.
Smart Images

Figure GDA0004797785560000021 
Figure GDA0004797785560000081 
Figure GDA0004797785560000082
Abstract
Description
Technical field:
[0001] The invention relates to a medical device. Background technology:
[0002] Currently, implantable medical devices are usually made of metals and their alloys, ceramics, polymers and other materials. Among them, metal materials are particularly popular because of their superior mechanical properties, such as high strength and high toughness. However, the corrosion of metal materials may bring two disadvantages: one is the generation of solid corrosion products, which are difficult to be absorbed / metabolized after long-term retention in the body, such as iron-based materials; the other is that higher metal ion concentrations may be toxic, such as the generation of zinc ions by zinc corrosion.
[0003] Iron is an important element in the human body and is involved in many biochemical processes, such as oxygen transportation. Peuster M et al. used pure iron as the material and used a laser engraving method to make a pure iron stent similar in shape to the metal stents used in clinical practice, and implanted it into the descending aorta of New Zealand rabbits. The results showed that no thrombotic complications or adverse events occurred within 6 to 18 months of implantation of the pure iron stent. Pathological examination confirmed that there was no inflammatory response in the local blood vessel wall and no obvious proliferation of smooth muscle cells, indicating that implantable devices made of iron-based materials have good application prospects. In the prior art, after the absorbable implantable medical device made of pure iron or iron-based alloy is implanted in the body, the iron-based matrix gradually corrodes in the physiological solution to generate corrosion products, including metal ions and Fe(OH) 3 、FeOOH、Fe 2 O 3 , Fe 3 O 4 , Fe 3 (PO 4 ) 2 Solid corrosion products such as iron and steel. These solid corrosion products have low solubility and are difficult to dissolve in body fluids. They mostly exist in the form of loose precipitation and are difficult to be absorbed / metabolized by tissues, which results in a long absorption cycle of medical devices. At the same time, they will remain in tissues for a long time. Iron-based medical devices corrode in the body to generate solid corrosion products. Although these particles can be absorbed and metabolized through the flow of intercellular fluid and phagocytosis by macrophages, the process takes a long time, which greatly prolongs the absorption cycle of implanted medical devices.
[0004] In addition, metal corrosion will also generate free metal ions, which will produce cytotoxicity when the metal ion concentration is too high. It has been reported that the cytotoxicity (median lethal dose) of zinc ions to fibroblasts, smooth muscle cells and endothelial cells is 50 μmol / L, 70 μmol / L and 265 μmol / L, respectively.
[0005] Ligands are also called ligands and complexing agents. The ligand structure contains lone pairs of electrons or π electrons as coordination groups, which can react with metal ions to form water-soluble coordination compounds, reduce the concentration of free metal ions, and reduce solid corrosion products (Equation (1)).
[0006]
[0007] The prior art discloses that the ligand is applied to iron-based alloy medical devices through physical mixing, which can complex iron corrosion products to a certain extent to form water-soluble iron complexes, which helps to remove iron corrosion products. However, in actual applications, due to factors such as the solubility and carrying capacity of the complexing agent, complexing agents are rarely used. For example, water-soluble ligands dissolve and disappear rapidly in body fluids, while the corrosion cycle of iron is as long as more than 1 year; secondly, the ligand is difficult to form a film and is difficult to load on the surface of medical devices in large quantities. Summary of the invention:
[0008] Based on this, it is necessary to provide a medical device.
[0009] A medical device includes a corrodible metal matrix and a ligand-degradable polymer. The ligand-degradable polymer is obtained by reacting a degradable polymer with a ligand. The ligand-degradable polymer can degrade and release a coordination group. The coordination group can react with the corrosion product produced by the corrodible metal matrix under a physiological environment to generate a water-soluble coordination compound.
[0010] The details of one or more embodiments of the invention are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the invention will become apparent from the description, drawings, and claims. Specific implementation method:
[0011] To facilitate understanding of the present invention, the present invention will be described more fully below.
[0012] A medical device in one embodiment includes a corrodible metal matrix and a ligand-degradable polymer, wherein the ligand-degradable polymer is obtained by reacting a degradable polymer with a ligand, and the ligand-degradable polymer can degrade and release a coordination group, and the coordination group can react with the corrosion product produced by the corrodible metal matrix under a physiological environment to generate a water-soluble coordination compound.
[0013] Further, the material of the corrodible metal matrix is selected from at least one of Fe, Zn, Mg, iron alloy, zinc alloy and magnesium alloy. Specifically, the corrodible metal matrix is an iron alloy or a zinc alloy. Further, the iron alloy is at least one of an iron-carbon alloy and a nitrided iron alloy. In some embodiments, the iron alloy may also be an iron-based alloy doped with at least one of O, S, P, Mn, Pd, Si, W, Ti, Co, Cr, Cu, and Re; the zinc alloy is a zinc-based alloy doped with at least one of C, N, O, S, P, Ce, Mn, Ca, Cu, Pd, Si, W, Ti, Co, Cr, Cu, and Re. The mass percentage of Fe in the iron alloy is 50% to 99.99%. The mass percentage of Zn in the zinc alloy is 50% to 99.99%.
[0014] In one embodiment, the corrosion product is a metal ion. Specifically, the metal ion includes at least one of iron ions, zinc ions and magnesium ions.
[0015] In one embodiment, the corrosion products also include solid corrosion products. Further, the solid corrosion products are usually Fe(OH) 3 、FeOOH、Fe 2 O 3 , Fe 3 O 4 .
[0016] In one embodiment, the volume ratio of the ligand-degradable polymer to the corrodible metal matrix is 0.1:1 to 20:1.
[0017] When a medical device is implanted in a living body, the corrodible metal matrix corrodes to generate metal ions or solid corrosion products, and the coordination groups in the ligand-degradable polymer react with the metal ions or solid corrosion products under physiological conditions to generate water-soluble coordination compounds. Compared with poorly soluble solid corrosion products, water-soluble coordination compounds can be metabolized and absorbed by the organism more quickly, which is beneficial to the recovery of the lesion site. At the same time, water-soluble coordination compounds can greatly degrade the concentration of free metal ions and reduce the risk of metal ions producing cytotoxicity.
[0018] The medical device may be a vascular stent, a non-vascular intraluminal stent, an occluder, an orthopedic implant, a dental implant, a respiratory implant, a gynecological implant, an andrological implant, a suture or a bolt. The non-vascular intraluminal stent may be a tracheal stent, an esophageal stent, a urethral stent, an intestinal stent or a biliary stent. The orthopedic implant may be a fixing screw, a fixing rivet or a bone plate. Of course, other medical devices that need to be degradable and absorbable may be used as the medical device of this embodiment.
[0019] It is understood that both the ligand-degradable polymer and the corrodible metal matrix are biologically acceptable and can be implanted in a living organism.
[0020] In some embodiments, the ligand-degradable polymer is at least partially in contact with the corrodible metal substrate. Further, the contact between the ligand-degradable polymer and the corrodible metal substrate may be any one or more of the following.
[0021] (1) The ligand-degradable polymer forms a coating on the surface of the corrodible metal substrate. Furthermore, the coating is formed by configuring the ligand-degradable polymer into a ligand-degradable polymer solution, and covering the ligand-degradable polymer solution on the surface of the corrodible metal substrate by spraying, dipping, brushing or electrospinning. Of course, the coating can only cover part of the surface of the corrodible metal substrate, or it can cover the entire surface of the corrodible metal substrate. In some embodiments, the ligand-degradable polymer solution also contains an active drug, so that the obtained coating contains a ligand-degradable polymer and an active drug mixed with the ligand-degradable polymer. The coating covers 5% to 100% of the surface of the corrodible metal substrate. Preferably, the coating covers 100% of the surface of the corrodible metal substrate. The thickness of the coating is flexibly set according to the specific type of medical device. For example, the size of the coronary stent is small, and the coating thickness does not exceed 70 microns, while the coating thickness in the fixed plate can reach 1 mm.
[0022] (2) The corrodible metal substrate is provided with a receiving portion, and the ligand-degradable polymer is received in the receiving portion. In some embodiments, the receiving portion is a groove formed on the surface of the corrodible metal substrate, in some embodiments, the receiving portion is a gap formed by the corrodible metal substrate, and in some embodiments, the receiving portion is an inner cavity formed by the corrodible metal substrate. Furthermore, the medical device also includes an active drug, which is mixed with the ligand-degradable polymer and received in the receiving portion.
[0023] In some embodiments, the medical device is loaded with an active drug. Further, the active drug is mixed with a ligand-degradable polymer. Specifically, the above two methods can be used to load the active drug onto a corrodible metal substrate.
[0024] Active drugs can be flexibly set according to the application scenarios and specific needs of medical devices. In one embodiment, the active drug is selected from at least one of drugs that inhibit angiogenesis, antiplatelet drugs, antithrombotic drugs, anti-inflammatory drugs and anti-allergic drugs. The drug that inhibits angiogenesis is selected from at least one of paclitaxel, rapamycin and its derivatives. The antiplatelet drug can be cilostazol. The antithrombotic drug can be heparin. The anti-inflammatory drug can be dexamethasone. The anti-allergic drug is selected from at least one of calcium gluconate, chlorpheniramine and cortisone. It should be noted that the drugs listed above are only exemplary examples, and the selection of various drugs is not limited to the specific drugs listed above, and can be flexibly selected according to needs.
[0025] In one embodiment, the ligand-degradable polymer includes a degradable polymer and a ligand connected to the degradable polymer. In some embodiments, the ligand-degradable polymer is obtained by reacting a degradable polymer with a ligand. Further, the ligand-degradable polymer is a copolymer of a degradable polymer and a ligand. In the human body environment, the ligand-degradable polymer can degrade and release the coordination group as it degrades. Further, the copolymer can be an alternating copolymer, a random copolymer, a block copolymer or a graft copolymer.
[0026] In some embodiments, the weight average molecular weight of the degradable polymer is 10,000 to 2,000,000.
[0027] In one embodiment, the degradable polymer is a degradable polyester.
[0028] In one embodiment, the degradable polyester is selected from at least one of polylactic acid, polyglycolic acid, polylactic glycolic acid, polycaprolactone, polyhydroxyalkanoate, polyacrylate, polysuccinate, poly(β-hydroxybutyrate), polydioxanone and polytrimethylene carbonate.
[0029] In one embodiment, the degradable polyester is selected from a degradable copolymer, wherein the degradable copolymer is selected from a copolymer formed by copolymerizing at least two of the monomers forming polylactic acid, polyglycolic acid, polylactic glycolic acid, polycaprolactone, polyhydroxyalkanoate, polyacrylate, polysuccinate, poly(β-hydroxybutyrate), polydioxanone and polytrimethylene carbonate. It should be noted that other materials that can bind to ligands, can be degraded and are biologically safe can be used as degradable polymers.
[0030] In some embodiments, the mass percentage of the ligand in the ligand-degradable polymer is 5% to 80%. If the mass percentage of the ligand is less than 5%, the amount of coordination groups released by the degradation of the ligand-degradable polymer is too small, so it can only complex a small amount of corrosion products, which is of little practical significance; if the mass percentage of the ligand is greater than 80%, the structure of the degradable polymer may be destroyed.
[0031] The ligand can react with the corrosion products produced by the corrodible metal matrix under physiological conditions to form a water-soluble coordination compound. In some embodiments, the solubility of the water-soluble coordination compound in a PBS buffer at 36°C to 38°C is ≥10 mg / L. Further, the solubility of the water-soluble coordination compound in a PBS buffer at 36°C to 38°C is 10 mg / L to 100 mg / L. When the solubility of the coordination compound in a physiological solution is greater than or equal to 100 mg / L, it indicates that the coordination compound can diffuse and metabolize rapidly in a physiological environment. When the solubility of the coordination compound in a physiological solution ranges from 10 mg / L to 100 mg / L, although the coordination compound will precipitate when the concentration of the coordination compound in the solution reaches saturation, as the coordination compound dissolved in the physiological solution gradually diffuses and is absorbed and metabolized by animal tissues, the dissolution equilibrium is broken, and the precipitated coordination compound will dissolve again until all the coordination compounds are completely dissolved and absorbed and metabolized by tissues. Therefore, this embodiment defines a coordination compound having a solubility in a physiological solution greater than or equal to 10 mg / L as a water-soluble coordination compound.
[0032] In one embodiment, the coordination group contains at least one of an amino group, a carboxyl group, a cyanide group, a thiocyanate group, an isothiocyanate group, a nitro group, a hydroxyl group, a phenolic hydroxyl group, a thiol group (-SH), a carbonyl group, an aromatic heterocyclic group, a nitroso group, a sulfonate group, a phosphoric acid group, and an organic phosphine group. Further, the coordination group contains at least one of an amino group and a carboxyl group. Further, the carbonyl-containing ligand is selected from at least one of a carboxylic acid, a carboxylate, an anhydride, an ester, an amide, a polycarboxylic acid, and a polyanhydride.
[0033] Furthermore, the aromatic heterocyclic group is selected from at least one of furanyl, pyrrolyl, thienyl, imidazolyl, triazolyl, thiazolyl, pyridyl, pyridone, pyranyl, pyrone, pyrimidinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, phthalazinyl, pteridinyl, indolyl, purinyl and phenanthroline.
[0034] Furthermore, the ligand is a multidentate ligand containing at least two coordination groups, and the generated coordination groups can form chelates with metal ions. Furthermore, the generated coordination groups can form chelates with iron ions or zinc ions under physiological conditions.
[0035] In one embodiment, the multidentate ligand is at least one of a multidentate ligand containing a hydroxyl group on a condensed aromatic hydrocarbon, a multidentate ligand containing a thiol group, a multidentate ligand containing an amino group, a multidentate ligand containing an aromatic heterocyclic group, a multidentate ligand containing a nitroso group, a multidentate ligand containing a carbonyl group, a multidentate ligand containing a sulfone group, a multidentate ligand containing a phosphate group, a multidentate ligand containing an organic phosphine group, and a multidentate ligand containing a carbonyl group.
[0036] Further, the multidentate ligand containing hydroxyl groups on condensed aromatic hydrocarbons is selected from at least one of 8-hydroxyquinoline, 8-hydroxyquinaldine, sodium 4,5-dihydroxybenzene-1,3-disulfonate and 4-[3,5-di-hydroxyphenyl-1H-1,2,4-triazole]-benzoic acid (deferiprole). The multidentate ligand containing thiol groups is selected from at least one of 8-mercaptoquinoline, thioglycolic acid and methyl 5-methyl-2-mercaptobenzoate. The multidentate ligand containing amino groups is selected from at least one of ethylenediamine, butanediamine, spermidine, spermine, triethylenetetramine, ethylenediaminetetraacetic acid, tetrasodium ethylenediaminetetraacetate and N'-[5-[[4-[[5-(acetylhydroxyamino)pentyl]amino]-1,4-dioxybutyl]hydroxylamine]pentyl]-N-(5-aminopentyl)-N-hydroxysuccinamide (deferoxamine). The polydentate ligand containing an aromatic heterocyclic group is selected from at least one of o-phenanthroline, bipyridine, porphyrin, porphine, chlorophyll, hemoglobin and 1,2-dimethyl-3-hydroxy-4-pyridone (deferiprone). The polydentate ligand containing a nitroso group is selected from at least one of 1-nitroso-2-naphthol and 1-nitroso-2-naphthol-6-sodium sulfonate. The polydentate ligand containing a carbonyl group is selected from at least one of polycarboxylic acids and their salts, anhydrides, esters, amides, polycarboxylic acids and polyanhydrides. The polydentate ligand containing a sulfonic group is selected from at least one of sulfosalicylic acid and 8-hydroxyquinoline-5-sulfonic acid. The polydentate ligand containing a phosphoric acid group is selected from at least one of pyrophosphate, tripolyphosphate, hexametapolyphosphate, polyphosphoric acid, sodium pyrophosphate, sodium hexametapolyphosphate and ammonium polyphosphate. The polydentate ligand containing an organic phosphine group is selected from at least one of diethylenetriamine penta (methylene phosphonic acid) potassium and ethylenediamine tetra (methylene phosphonic acid) sodium. The carbonyl-containing multidentate ligand is selected from at least one of oxalic acid, tartaric acid, malic acid, succinic acid, oxaloacetic acid, fumaric acid, maleic acid, citric acid, nitrilotriacetic acid, diethylenetriaminepentacarboxylic acid, alginic acid, glutamic acid, aspartic acid, ornithine, lysine, maleic anhydride, acetic anhydride, maleic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, potassium citrate, calcium citrate, glyceryl citrate, acetylsalicylic acid, sulfosalicylamide, polyaspartic acid, polyglutamic acid, polyornithine, polylysine and polymaleic anhydride.
[0037] In one embodiment, the multidentate ligand is selected from at least one of amino acids, oligopeptides, polypeptides, proteins, polyamines, anhydrides and polyanhydrides containing amino or carboxyl groups. Among them, peptides are compounds formed by connecting amino acids with peptide bonds after dehydration. Peptides composed of 2 to 10 amino acids are called oligopeptides, peptides composed of 10 to 50 amino acids are called polypeptides, and peptides composed of more than 50 amino acids are called proteins. Specifically, the amino acids are selected from at least one of glycine, alanine, valine, leucine, isoleucine, phenylalanine, tryptophan, tyrosine, aspartic acid, asparagine, glutamic acid, lysine, glutamine, methionine, serine, threonine, ornithine, cysteine, proline, histidine and arginine.
[0038] In one embodiment, the ligand is selected from polysaccharides containing multiple hydroxyl groups. Specifically, the polysaccharide is selected from at least one of dextran, chitosan, plant polysaccharides, starch, dextrin, cellulose, glycogen, chitin, chitosan, inulin, agar, gum arabic, hyaluronic acid, gellan gum, calendulum, xanthan gum, pectin, konjac glucomannan, gum arabic, seaweed lichen polysaccharide, alginate, spirulina polysaccharide, chondroitin sulfate, dermatan sulfate, keratan sulfate, heparin and heparan sulfate.
[0039] In some embodiments, the ligand-degradable polymer is obtained by reacting the ligand with the degradable polymer, and the ligand contains a carbon-carbon double bond (=). Specifically, the ligand is selected from at least one of 2-amino-4-pentenoic acid, 2-acetamidoacrylic acid, maleic acid, fluocinol, allyl oxalate, octenylsuccinic acid, diethylenetriamine pentacarboxylic acid and maleic anhydride. The degradable polymer can be a general degradable polymer that can react with the ligand. More preferably, the degradable polymer is the degradable polymer listed above.
[0040] The ligand contains a carbon-carbon double bond (=), which can provide a lone pair of electrons required for a free radical reaction. When exposed to light, radiation, peroxide, etc., the carbon-carbon double bond can react with the degradable polymer to produce a ligand-degradable polymer. The specific reaction is shown in reaction formulas (1) and (2).
[0041]
[0042] The wavy line represents a degradable polymer, and R represents H or a hydrocarbon group.
[0043] In some embodiments, the ligand does not contain a carbon-carbon double bond (=), and after the ligand is combined with a compound containing a carbon-carbon double bond, it is reacted with a degradable polymer to obtain a ligand-degradable polymer. Specifically, the ligand is selected from at least one of an acid, an ester, an amide, an amine, an amino acid, a peptide, and a protein. The compound containing a carbon-carbon double bond is selected from at least one of vinyl isocyanate, ethylene acetic acid, vinyl acetate, vinyl sulfonic acid, versatate, vinyl sorbate, acrylic acid, methyl acrylate, and acrylamide.
[0044] Of course, in some embodiments, the first reactive group can also be grafted onto a degradable polymer as a degradable polymer intermediate, and reacted with a ligand containing a second reactive group to obtain a ligand-degradable polymer. The first reactive group can react with the second reactive group. At least one of the first reactive group and the second reactive group can release a coordination group. Further, one of the first reactive group and the second reactive group is selected from at least one of an isocyanate group, a carboxyl group, an acyl chloride group, and an epoxy group, and the other is selected from at least one of an amino group, a hydroxyl group, a thiol group, and a carboxyl group. Of course, it should be noted that the first reactive group and the second reactive group are not limited to the groups listed above, as long as they can react with each other to be modified to obtain a ligand-degradable polymer, and can release a coordination group that reacts with metal ions or solid corrosion products under a physiological environment to form a water-soluble coordination compound.
[0045] Specifically, one of the first reactive group and the second reactive group is an amino group, and the other is at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group; one of the first reactive group and the second reactive group is a hydroxyl group, and the other is at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group; one of the first reactive group and the second reactive group is a thiol group, and the other is at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group; one of the first reactive group and the second reactive group is a carboxyl group, and the other is at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group; one of the first reactive group and the second reactive group is an isocyanate group, and the other is at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group; one of the first reactive group and the second reactive group is a carboxyl group, and the other is at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group; one of the first reactive group and the second reactive group is an acyl chloride group, and the other is at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group; one of the first reactive group and the second reactive group is an epoxy group, and the other is at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group. The reaction formula of the reaction of at least one of an amino group, a hydroxyl group, a mercapto group and a carboxyl group with at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group is as shown in the following expressions (3) to (11).
[0046]
[0047] In the expressions (3) to (11), R, R', and R" each independently represent H or a hydrocarbon group.
[0048] In some embodiments, the ligand contains at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group, and the ligand-degradable polymer is obtained by reacting the ligand with a degradable polymer intermediate. The degradable polymer intermediate contains at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group. Further, the ligand is selected from ethylenediamine, butanediamine, spermidine, spermine, triethylenetetramine, ethylenediaminetetraacetic acid, tetrasodium ethylenediaminetetraacetic acid, N'-[5-[[4-[[5-(acetylhydroxyamino)pentyl]amino]-1,4-dioxybutyl]hydroxylamine]pentyl]-N-(5-aminopentyl)-N-hydroxysuccinamide (deferoxamine), 8-hydroxyquinoline, 8-hydroxyquinaldine, 4,5-dihydroxybenzene-1,3-disulfonic acid sodium, 4-[3,5-di-hydroxyphenyl-1H-1,2,4-triazole]-benzoic acid (deferoxamine), 8-mercaptoquinone At least one of phenoxyethanol, thioglycolic acid, 5-methyl-2-mercaptobenzoic acid methyl ester, oxalic acid, tartaric acid, malic acid, succinic acid, oxaloacetic acid, fumaric acid, maleic acid, citric acid, nitrilotriacetic acid, diethylenetriamine pentacarboxylic acid, alginic acid, glutamic acid, aspartic acid, ornithine, lysine, maleic anhydride, acetic anhydride, maleic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, potassium citrate, calcium citrate, glyceryl citrate, acetylsalicylic acid, sulfosalicylamide, polyaspartic acid, polyglutamic acid, polyornithine, polylysine and polymaleic anhydride.
[0049] The degradable polymer is grafted with at least one grafting compound containing isocyanate, carboxyl, acyl chloride and epoxy to obtain a degradable polymer intermediate. The grafting compound is selected from at least one of vinyl isocyanate, 3-isocyanate propylene, maleic anhydride, acrylic acid, methacrylic acid, decenoic acid, 9-decenoic acid undecenoic acid, acryloyl chloride, methacryloyl chloride, crotonoyl chloride, crotonoyl chloride, undecenoyl chloride, ethylene oxide, butylene oxide and squalene oxide.
[0050] Of course, in some embodiments, the ligand contains at least one of isocyanate, carboxyl, acyl chloride and epoxy, and the ligand reacts with the degradable polymer intermediate to obtain the ligand-degradable polymer. The degradable polymer intermediate contains at least one of amino, hydroxyl, thiol and carboxyl. Further, the ligand is selected from at least one of isocyanate, oxalic acid, tartaric acid, malic acid, succinic acid, oxaloacetic acid, fumaric acid, maleic acid, citric acid, nitrilotriacetic acid, diethylenetriaminepentacarboxylic acid, alginic acid, glutamic acid, aspartic acid, ornithine, lysine, maleic anhydride, acetic anhydride, maleic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, potassium citrate, calcium citrate, glyceryl citrate, acetylsalicylic acid, sulfosalicylamide, polyaspartic acid, polyglutamic acid, polyornithine, polylysine, polymaleic anhydride, acetyl chloride, oxalyl chloride, acetylsalicylic acid chloride, succinic acid monomethyl chloride, succinic acid monoethyl chloride, succinic acid monomethyl chloride, succinic acid monoethyl chloride, epoxyacetic acid, epoxypropionic acid and epoxysuccinic acid.
[0051] The degradable polymer is grafted with at least one grafting compound containing amino, hydroxyl, thiol and carboxyl groups to obtain a degradable polymer intermediate. The grafting compound is selected from at least one of aminoethylene, aminopropylene, tetrakis(dimethylamino)ethylene, 2-amino-4-pentenoic acid, 10-hydroxy-2-decenoic acid, p-hydroxystyrene, 1,4-dihydroxy-2-butene, 3-butene-1-ol, mercaptopropionic acid, mercaptoacrylic acid, 3-enecarboxylic acid, cyclohexenecarboxylic acid, distyrene dicarboxylic acid and pyrrolidone carboxylic acid.
[0052] The above-mentioned medical device connects ligands to the chain segments of the degradable polymer to obtain a chemically modified ligand-degradable polymer, and then carries the modified degradable polymer on the surface of the absorbable and corrodible metal matrix. After the medical device is implanted in the body, the modified degradable polymer gradually degrades and releases the coordination group, and the coordination group reacts with the corrosion product after the corrosion of the corrodible metal matrix under the physiological environment to generate a water-soluble coordination compound, thereby reducing the concentration of free metal ions and the sparingly soluble solid corrosion products generated by the corrosion of the corrodible metal matrix, reducing the risk of metal ion cytotoxicity, accelerating the corrosion of the metal, and allowing the corrosion products to be quickly absorbed and metabolized by the tissue, which is beneficial to the recovery of the lesion site and reduces the possibility of adverse reactions caused by the long-term retention of corrosion products in the human body.
[0053] In the following embodiments, the weight average molecular weight of the ligand-degradable polymer is detected by using a molecular weight test system of GPC-multi-angle laser light scattering instrument of Wyatt, USA. The test system includes a liquid phase pump and injector of Agilent, USA, Agilent PL MIXED-C type GPC column (size: 7.5×300mm, 5 microns) of Agilent, USA, a multi-angle laser light scattering instrument and a differential detector of Wyatt, USA. The detection conditions are: mobile phase: tetrahydrofuran; pump flow rate: 1mL / min; injection volume: 100μL; laser wavelength: 663.9nm; test temperature: 35℃.
[0054] In the following embodiments, the mass fraction of the ligand in the ligand-degradable polymer is defined as the ratio between the molecular mass of the ligand and the total molecular mass of the ligand-degradable polymer.
[0055] The method for detecting the mass fraction of the ligand comprises the following steps: detecting the molar ratio of the key groups in the ligand and the key groups in the degradable polymer molecule respectively by a nuclear magnetic resonance apparatus (MRI), and then obtaining the mass fraction of the ligand by calculation according to the ratio.
[0056] The concentration of water-soluble coordination compounds at different stages is detected by the following method: the medical device is immersed in a phosphate buffer solution (PBS) with a pH range of 7.4±0.05, and the ratio of the volume of PBS to the enclosed volume of the medical device is 5-10:1. The medical device is required to be completely immersed in PBS. If the medical device is small and the immersion container is large, the number of medical devices can be increased. The physiological solution soaked with the medical device is placed in a 37±1°C constant temperature water bath environment and oscillated at a rate of 40 rpm to 80 rpm. At a predetermined observation time point, such as 7 days, 1 month, 3 months..., it is filtered with an aqueous membrane with a pore size of 0.22 μm to remove the insoluble substances in PBS, and then the mass concentration of the metal element in the filtered filtrate is detected by atomic absorption spectroscopy (AAS). The mass concentration of the water-soluble coordination compound in PBS at 37±1°C can be further obtained by conversion. At the same time, the corroded medical device is placed in the same volume of PBS solution for further corrosion until the next observation time point. The experimental process is as described above. If metal elements are detected in the solution after a period of time after the solution is replaced, it means that the coordination groups are gradually released as the degradable polymer degrades.
[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0059] The present invention is further described in detail below in conjunction with specific embodiments, taking an iron-based alloy coronary stent as an example, but the scope of protection of the present invention is not limited thereto.
[0060] It should be pointed out that in the following embodiments, due to normal fluctuations in the product's own performance within the design allowable range, differences in the corrosion rates of individual devices, and systematic errors inevitably introduced by the testing method, the concentration of the detected iron coordination compound will fluctuate within a certain range in actual testing.
[0061] Example 1
[0062] The medical device provided in Example 1 is an absorbable nitrided iron-based stent, comprising a stent matrix made of nitrided iron material, and a (2-amino-4-pentenoic acid)-polyracemic lactic acid (mPDLLA) coating covering the surface of the stent matrix, the wall thickness of the stent matrix is 50 μm, and the thickness of the coating is 60 μm. The volume ratio of the coating to the stent matrix is 10.56:1. The coating covers 100% of the surface of the stent matrix.
[0063] The preparation process of the absorbable nitrided iron-based scaffold provided in Example 1 is as follows: mPDLLA is dissolved in ethyl acetate, and the solution is sprayed onto the surface of the nitrided iron-based scaffold, and dried to obtain the absorbable nitrided iron-based scaffold of Example 1.
[0064] The preparation method of mPDLLA comprises the following steps: dissolving polyracemic lactic acid (PDLLA for short), 2-amino-4-pentenoic acid and DCP in a mass ratio of 50:50:5 in tetrahydrofuran, stirring and reacting for 15 hours in an anhydrous and oxygen-free environment at 60°C, and the obtained product is mPDLLA, which is purified and dried by a methanol-chloroform system. The mPDLLA used in Example 1 is obtained. The molecular structure of mPDLLA is shown below.
[0065]
[0066] During the preparation process, the ligand 2-amino-4-pentenoic acid contains a carbon double bond, and the 2-amino-4-pentenoic acid is covalently grafted onto the PDLLA segment through a double bond free radical reaction to form a modified PDLLA.
[0067] The weight average molecular weight of mPDLLA used in Example 1 was measured to be 200,000 Da. The mass fraction of the ligand in mPDLLA was 46%.
[0068] Using the same raw materials and methods, 5 identical absorbable iron-based stents were made, and the 5 stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 80 rpm. Then the concentration of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 1 was soaked in PBS at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 146 mg / L. After soaking for 1 month, the concentration of the iron coordination compound in PBS was 650 mg / L. After soaking for 3 months, the concentration of the iron coordination compound in PBS was 1500 mg / L.
[0069] Example 2
[0070] The medical device provided in Example 2 is an absorbable iron-based stent, including a stent matrix made of pure iron material, and a salicylic acid-vinyl isocyanate-polylactic acid-glycolic acid copolymer (mPLGA) coating covering the surface of the stent matrix. The wall thickness of the stent matrix is 70 μm, and the thickness of the mPLGA coating is 4 μm. The volume ratio of the coating to the stent matrix is 0.17:1. The coating covers 70% of the surface of the stent matrix.
[0071] The manufacturing process of the absorbable iron-based stent provided in Example 2 is as follows: mPLGA is uniformly applied to the surface of the pure iron stent by spraying to obtain the absorbable iron-based stent of Example 2.
[0072] The preparation method of mPLGA comprises the following steps: dissolving salicylic acid and vinyl isocyanate in a molar ratio of 1:1 in chloroform and mixing them evenly, stirring and reacting at room temperature for 12 hours, and the obtained product vinyl isocyanate-salicylic acid is vacuum dried for use; polylactic acid-glycolic acid copolymer (referred to as PLGA), vinyl isocyanate-acetylsalicylic acid and BPO are dissolved in toluene in a mass ratio of 70:30:2, stirring and reacting for 6 hours in anhydrous and oxygen-free environment at 110°C, and the obtained product is mPLGA, which is purified and dried by a methanol-chloroform system to obtain the mPLGA used in Example 1. The molecular structure of mPLGA is shown below.
[0073]
[0074] In the preparation process, firstly, vinyl isocyanate containing double bonds is grafted onto the ligand salicylic acid, and then it participates in free radical reaction through the double bonds and is grafted onto the PLGA chain segment.
[0075] The weight average molecular weight of mPLGA used in Example 2 was measured to be 150,000 Da, and the mass fraction of the ligand was 30%.
[0076] Using the same raw materials and methods, 5 identical absorbable iron-based stents were made, and the 5 stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 60 rpm. Then the concentration of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 2 was soaked in PBS at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 50 mg / L. After soaking for 1 month, the concentration of the iron coordination compound in PBS was 300 mg / L. After soaking for 3 months, the concentration of the iron coordination compound in PBS was 1000 mg / L. The results show that by grafting salicylic acid to polylactic acid, the ligand can exist for a long time and gradually release, and chelate with iron ions to form chelated iron, reducing solid corrosion products.
[0077] Example 3
[0078] The medical device provided in Example 3 is an absorbable iron-based stent, including a stent matrix made of pure iron material, and a glycine-maleic anhydride-polycaprolactone (mPCL) coating covering the surface of the stent matrix. The wall thickness of the stent matrix is 50 μm, and the thickness of the mPCL coating is 6 μm. The volume ratio of the coating to the stent matrix is 0.54:1. The coating covers 100% of the surface of the stent matrix.
[0079] The manufacturing process of the absorbable iron-based stent provided in Example 3 is as follows: mPCL is uniformly applied to the surface of the pure iron stent by spraying to obtain the absorbable iron-based stent of Example 3.
[0080] The preparation method of mPCL comprises the following steps: polycaprolactone (PCL for short), maleic anhydride (MAH for short) and benzoyl peroxide (BPO for short) in a mass ratio of 90:10:0.5 are dissolved in chloroform and mixed evenly to obtain a mixture. After the mixture is dried, it is reacted under nitrogen protection at 100°C for 10 hours. The obtained product is purified by a methanol-chloroform system and then vacuum dried to obtain a modified polycaprolactone intermediate (maleic anhydride-polycaprolactone). The obtained maleic anhydride-polycaprolactone is dissolved in tetrahydrofuran, and then added dropwise to a tetrahydrofuran solution of aminoacetic acid (glycine) to obtain a crude product of mPCL. The crude product of mPCL is purified and dried by a methanol-chloroform system to obtain the mPCL used in Example 3. The molecular structure of mPCL is shown below.
[0081]
[0082] During the preparation process, maleic anhydride containing a carbon double bond is first grafted onto polycaprolactone through a free radical reaction to obtain a modified polycaprolactone intermediate, which contains a carboxyl group. The carboxyl group reacts with the amino group in the ligand amino acid to obtain glycine-maleic anhydride-polycaprolactone.
[0083] The weight average molecular weight of mPCL used in Example 3 was measured to be 100,000 Da, and the mass fraction of the ligand was 20%.
[0084] Using the same raw materials and methods, 5 identical absorbable iron-based stents were made, and the 5 stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 60 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 3 was immersed in PBS at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 20 mg / L. After immersion for 1 month, the concentration of the iron coordination compound in PBS was 100 mg / L. After immersion for 3 months, the concentration of the iron coordination compound in PBS was 500 mg / L. The results show that by grafting glycine to polycaprolactone, glycine can exist for a long time and gradually release, and chelate with iron ions to form chelated iron, reducing solid corrosion products.
[0085] Example 4
[0086] The medical device provided in Example 4 is an absorbable iron-based stent, including a stent matrix made of nitrided iron material, and a rapamycin-(8-hydroxyquinoline-2-carboxylic acid)-acryloyl chloride-polyglycolic acid (abbreviated as mPGA) coating covering the surface of the stent matrix, the wall thickness of the stent matrix is 60 μm, and the thickness of the coating is 20 μm. The volume ratio of the coating to the stent matrix is 1:1. The coating covers 50% of the surface of the stent matrix.
[0087] The preparation process of the absorbable iron-based stent provided in Example 4 is as follows: mPGA and rapamycin in a mass ratio of 5:1 are mixed and dissolved in ethyl acetate, and the solution is sprayed onto the surface of the pure iron stent and dried to obtain the absorbable iron-based alloy stent of Example 4.
[0088] The preparation method of mPGA comprises the following steps: dissolving 8-hydroxyquinoline-2-carboxylic acid and acryloyl chloride in a molar ratio of 1:1 in chloroform and mixing them evenly, stirring and reacting at room temperature for 12 hours, and the obtained product 8-hydroxyquinoline-2-carboxylic acid-acryloyl chloride is vacuum dried for standby use; polyglycolic acid (PGA for short), 8-hydroxyquinoline-2-carboxylic acid-acryloyl chloride and diisopropylbenzene peroxide (DCP for short) are dissolved in toluene in a mass ratio of 60:40:3, stirring and reacting for 6 hours in anhydrous and oxygen-free environment at 110°C, and the obtained product is mPLA, which is purified and dried by a methanol-chloroform system to obtain mPGA used in Example 4. The molecular structure of mPGA is shown below.
[0089]
[0090] In the modification process, acryloyl chloride containing double bonds is first grafted onto the ligand 8-hydroxyquinoline-2-carboxylic acid, and then it participates in the free radical reaction through the double bonds and is grafted onto the PGA chain segment. (8-hydroxyquinoline-2-carboxylic acid)-acryloyl chloride-polyglycolic acid will gradually degrade in the body, and the ligand 8-hydroxyquinoline-2-carboxylic acid will be gradually released and chelate with iron ions to form 8-hydroxyquinoline-2-carboxylic acid iron.
[0091] The weight average molecular weight of mPLA used in Example 4 was measured to be 100,000 Da, and the mass fraction of the ligand was 37%.
[0092] Using the same raw materials and methods, five identical absorbable iron-based stents were made, and the five stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 60 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 4 was immersed in PBS at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 100 mg / L. After immersion for 1 month, the concentration of the iron coordination compound in PBS was 400 mg / L. After immersion for 3 months, the concentration of the iron coordination compound in PBS was 1000 mg / L. The results show that by grafting the ligand to polyglycolic acid, the ligand can exist for a long time and gradually release, and chelate with iron ions to form chelated iron, reducing solid corrosion products.
[0093] Example 5
[0094] The medical device provided in Example 5 is an absorbable nitrided iron-based stent, including a stent matrix made of nitrided iron material, a zinc layer covering the surface of the stent matrix, and an ethylenediaminetetraacetic acid-acryloyl chloride-polylactic acid (mPLA) coating covering the surface of the zinc layer. The wall thickness of the stent matrix is 50 μm, the thickness of the zinc layer is 1.5 μm, and the thickness of the coating is 10 μm. The volume ratio of the coating, the zinc layer and the stent matrix is 1.13:0.12:1. The coating covers 100% of the surface of the stent matrix. The zinc layer covers 100% of the surface of the stent matrix.
[0095] The preparation process of the absorbable nitrided iron-based stent provided in Example 5 is as follows: a layer of zinc layer is covered on the surface of the nitrided iron-based stent by electroplating; then mPLA is dissolved in ethyl acetate, and the solution is sprayed onto the surface of the galvanized iron-based stent, and dried to obtain the absorbable nitrided iron-based stent of Example 5.
[0096] The preparation method of mPLA comprises the following steps: dissolving ethylenediaminetetraacetic acid (EDTA for short) and acryloyl chloride in a molar ratio of 1:1 in chloroform and mixing them evenly, stirring and reacting at room temperature for 12 hours, and the obtained product ethylenediaminetetraacetic acid-acryloyl chloride is vacuum dried for standby use; polylactic acid (PLA for short), ethylenediaminetetraacetic acid-acryloyl chloride and di-tert-butyl peroxide (DBP) are dissolved in toluene in a mass ratio of 35:65:6, stirring and reacting for 18 hours in anhydrous and oxygen-free environment at 120°C, and the obtained product is mPLA, which is purified and dried by a methanol-chloroform system to obtain mPLA used in Example 5. The molecular structure of mPLA is shown below.
[0097]
[0098] In the modification process, acryloyl chloride containing double bonds is first grafted onto the ligand EDTA, and then it participates in free radical reaction through double bonds and is grafted onto the PLA segment. EDTA-acryloyl chloride-PLA will gradually degrade in the body, and the ligand EDTA will be gradually released and chelate with iron ions to form EDTA iron.
[0099] The weight average molecular weight of mPLA used in Example 5 was measured to be 200,000 Da, and the mass fraction of the ligand was 60%.
[0100] Using the same raw materials and methods, 5 identical absorbable iron-based stents were made, and the 5 stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 60 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 5 was soaked in PBS at 37°C for 7 days, the concentrations of zinc and iron coordination compounds in PBS were 300 mg / L and 0 mg / L, respectively. After soaking for 1 month, the concentrations of zinc and iron coordination compounds in PBS were 200 mg / L and 400 mg / L, respectively. After soaking for 3 months, the concentrations of zinc and iron coordination compounds in PBS were 200 mg / L and 1200 mg / L, respectively. The results show that by grafting the ligand to the polyester, the ligand can exist for a long time and be gradually released, chelating with zinc ions in the early stage to reduce the concentration of free zinc ions, and chelating with iron ions in the middle and late stages to reduce iron solid corrosion products.
[0101] Example 6
[0102] The medical device provided in Example 6 is an absorbable nitrided iron-based stent, including a stent matrix made of nitrided iron material, and a dextran-poly racemic lactic acid (mPDLLA) coating covering the surface of the stent matrix, the wall thickness of the stent matrix is 50 μm, and the thickness of the coating is 20 μm. The volume ratio of the coating to the stent matrix is 2.24:1. The coating covers 100% of the surface of the stent matrix.
[0103] The preparation process of the absorbable nitrided iron-based scaffold provided in Example 6 is as follows: a layer of zinc layer is covered on the surface of the nitrided iron-based scaffold by electroplating; then, dextran-polyracemic lactic acid (mPDLLA for short) is dissolved in ethyl acetate, and the solution is sprayed onto the surface of the galvanized iron-based scaffold, and dried to obtain the absorbable nitrided iron-based scaffold of Example 6.
[0104] The preparation method of mPDLLA comprises the following steps: dissolving dextran 5W and PDLLA at a molar ratio of 1:1 in dimethyl sulfoxide, and copolymerizing them under the activation of epichlorohydrin, and the obtained product dextran-PDLLA is mPDLLA, which is purified by acetone and dried to obtain mPDLLA used in Example 6. The molecular structure of mPDLLA is shown below.
[0105]
[0106] During the modification process, the two structural units of dextran and poly(racemic lactic acid) are randomly and alternately connected. Dextran-poly(racemic lactic acid) will gradually degrade in the body, and dextran will gradually degrade and release, chelating with iron corrosion products to form dextran-iron complex.
[0107] The weight average molecular weight of mPLA used in Example 6 was measured to be 200,000 Da, and the mass fraction of the ligand was 50%.
[0108] Using the same raw materials and methods, 5 identical absorbable iron-based stents were made, and the 5 stents were soaked together in PBS with a volume of 5 times the volume of the stent. Then the PBS soaked with the stent was placed in a 37°C constant temperature water bath environment and oscillated at a rate of 60 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the medical device of Example 5 was immersed in PBS at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 500 mg / L. After immersion for 1 month, the concentration of the iron coordination compound in PBS was 1000 mg / L. After immersion for 3 months, the concentration of the iron coordination compound in PBS was 1800 mg / L. The results show that by copolymerizing the ligand with the polyester, the ligand can exist for a long time and gradually release, chelating with iron ions to reduce iron solid corrosion products.
[0109] Comparative Example 1
[0110] Ordinary PLA was sprayed on the surface of the pure iron stent and dried to obtain the absorbable iron-based stent of Comparative Example 1. The wall thickness of the stent matrix was 50 μm, and the thickness of the PDLLA coating was 5 μm. The mass ratio of the coating to the stent matrix was 0.44:1. The coating covered 100% of the surface of the stent matrix.
[0111] By the aforementioned detection method, it was determined that the weight average molecular weight of PDLLA used in Comparative Example 1 was 200,000 Da.
[0112] Using the same raw materials and methods, 5 identical absorbable iron-based scaffolds were made, and the 5 scaffolds were soaked together in PBS with a volume of 5 times the volume of the scaffold. The PBS soaked with the scaffold was then placed in a 37°C constant temperature water bath environment and oscillated at a rate of 80 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the absorbable iron-based scaffold of Comparative Example 1 was soaked in a PBS solution at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 0 mg / L. After soaking for 1 month, the concentration of the iron coordination compound in PBS was 0 mg / L. After soaking for 3 months, the concentration of the iron coordination compound in PBS was 0 mg / L.
[0113] The results show that compared with the medical device provided in Example 1, the absorbable iron-based stent in Comparative Example 1 has poorly soluble corrosion products in the physiological environment due to the fact that the ordinary polylactic acid in Comparative Example 1 cannot react with iron ions under physiological conditions. In the medical device provided in Example 1, polylactic acid is chemically modified to form a ligand-polylactic acid having a ligand group, and the ligand-polylactic acid combines with iron ions in a physiological environment to form a water-soluble iron coordination compound.
[0114] Comparative Example 2
[0115] The surface of the pure iron stent was sprayed with a common 2-amino-4-pentenoic acid coating, and then with a PDLLA coating, and dried to obtain an absorbable iron-based stent of Comparative Example 2. The wall thickness of the stent matrix was 50 μm, the thickness of the 2-amino-4-pentenoic acid coating was 5 μm, and the thickness of the PDLLA coating was 5 μm. The mass ratio of the coating to the stent matrix was 0.96:1. The coating covered 100% of the surface of the stent matrix.
[0116] By the aforementioned detection method, it was determined that the weight average molecular weight of the PLA used in Comparative Example 2 was 200,000 Da, and the mass fraction of 2-amino-4-pentenoic acid was 50%.
[0117] Using the same raw materials and methods, 5 identical absorbable iron-based scaffolds were made, and the 5 scaffolds were soaked together in PBS with a volume of 5 times the volume of the scaffold. The PBS soaked with the scaffold was then placed in a 37°C constant temperature water bath environment and oscillated at a rate of 80 rpm. Then the solubility of the iron coordination compound in PBS was detected by AAS at 7 days, 1 month and 3 months of oscillation. The test results are as follows: After the absorbable iron-based scaffold of Comparative Example 2 was soaked in a PBS solution at 37°C for 7 days, the concentration of the iron coordination compound in PBS was 50 mg / L. After soaking for 1 month, the concentration of the iron coordination compound in PBS was 0 mg / L. After soaking for 3 months, the concentration of the iron coordination compound in PBS was 0 mg / L.
[0118] The results show that the absorbable iron-based stent of Comparative Example 2 is compared with the medical device provided in Example 1, because the polylactic acid and the ligand of Comparative Example 2 are only physically blended, the ligand diffuses rapidly in the body fluid and cannot exist on the surface of the stent for a long time. It can chelate a small amount of iron ions in the early stage, and there is no ligand in the middle and late stages after the liquid is changed, and no water-soluble chelated iron is generated. And because the ligand has poor film-forming properties, it is difficult to form a thick film on the surface of the corrodible metal matrix, the co-loading amount is small, and only a small amount of iron can be chelated.
[0119] Compared with the method of physically blending polylactic acid and ligands in comparative example 2, the chemical modification method of example 1 can make the ligand distribution in the ligand-degradable polyester more uniform, the binding force stronger, and the co-loading capacity larger, thereby ensuring the stable existence and function of the ligand and avoiding the loss of the ligand due to immersion or flushing in body fluids.
[0120] In summary, in the medical device of the present invention, a chemically modified ligand-degradable polymer is obtained by covalently grafting a ligand onto the chain segment of a degradable polymer, and then the ligand-degradable polymer is carried on the surface of a corrodible metal substrate. The coordination groups in the ligand-degradable polyester combine with corrosion products generated by corrosion of the corrodible metal substrate to generate water-soluble coordination compounds under a physiological environment, thereby reducing the insoluble solid corrosion products generated by the corrosion of the corrodible metal substrate, so that the water-soluble corrosion products of the corrodible metal substrate can be quickly absorbed and metabolized by tissues.
[0121] In addition, since the ligand and the degradable polymer are bound by covalent bonds, the binding mode between the ligand and the degradable polymer is more firm and reliable, and the ligand can be distributed more evenly in the ligand-degradable polymer, avoiding the loss of the ligand caused by flushing or immersion in body fluids.
Claims
1. A medical device, comprising a corrodible metal matrix and a ligand-degradable polymer, wherein the ligand-degradable polymer is obtained by reacting a degradable polymer with a ligand, the ligand-degradable polymer can degrade and release a coordination group, and the coordination group can react with the corrosion product produced by the corrodible metal matrix under a physiological environment to generate a water-soluble coordination compound; the material of the corrodible metal matrix is selected from at least one of Fe, Zn, Mg, iron alloy, zinc alloy and magnesium alloy; the degradable polymer is selected from degradable polyester; The ligand-degradable polymer is at least partially in contact with the corrodible metal substrate, and the ligand-degradable polymer forms a coating on the surface of the corrodible metal substrate, and the coating covers 50% to 100% of the surface of the corrodible metal substrate; the volume ratio of the ligand-degradable polymer to the corrodible metal substrate is 0.1:1 to 10.56:
1.
2. The medical device according to claim 1, characterized in that: The iron alloy is at least one of an iron-carbon alloy and a nitrided iron alloy.
3. The medical device according to claim 1, characterized in that: The degradable polyester is selected from at least one of polycaprolactone, polyhydroxyalkanoate, polyacrylate, polysuccinate, polydioxanone and polytrimethylene carbonate.
4. The medical device according to claim 1, characterized in that: The degradable polyester is selected from degradable copolymers, wherein the degradable copolymer is selected from copolymers formed by copolymerizing at least two monomers forming polycaprolactone, polyhydroxyalkanoate, polyacrylate, polysuccinate, polydioxanone and polytrimethylene carbonate.
5. The medical device according to claim 1, characterized in that: The degradable polyester is selected from at least one of polylactic acid, polyglycolic acid, polylactic glycolic acid, polycaprolactone, polyacrylate, polysuccinate, poly(β-hydroxybutyrate), polydioxanone and polytrimethylene carbonate.
6. The medical device according to claim 1, characterized in that: The degradable polyester is selected from degradable copolymers, wherein the degradable copolymer is selected from copolymers formed by copolymerization of at least two of the monomers forming polylactic acid, polyglycolic acid, polylactic glycolic acid, polycaprolactone, polyacrylate, polysuccinate, poly(β-hydroxybutyrate), polydioxanone and polytrimethylene carbonate.
7. The medical device according to claim 1, characterized in that: The solubility of the water-soluble coordination compound in a phosphate buffer at 36° C. to 38° C. is greater than or equal to 10 mg / L.
8. The medical device according to claim 1, characterized in that: The mass percentage of the corrodible metal matrix in the medical device is 50%.
9. The medical device according to claim 1, characterized in that: The mass percentage of the ligand in the ligand-degradable polymer is 5% to 80%.
10. The medical device according to claim 1, characterized in that: The coordination group contains at least one of an amino group, a carboxyl group, a cyanide group, a thiocyanate group, an isothiocyanate group, a nitro group, a hydroxyl group, a thiol group, an aromatic heterocyclic group, a nitroso group, a sulfone group, a phosphoric acid group and an organic phosphine group.
11. The medical device according to claim 1, characterized in that: The ligand is a polysaccharide.
12. The medical device according to claim 1, characterized in that: The ligand is a multidentate ligand containing at least two coordination groups.
13. The medical device according to claim 12, characterized in that: The multidentate ligand is selected from at least one of amino acids, oligopeptides, polypeptides, proteins, polyamines, anhydrides and polyanhydrides containing amino or carboxyl groups.
14. The medical device according to claim 1, characterized in that: The ligand contains a carbon-carbon double bond, and the ligand undergoes a free radical reaction with the degradable polymer via the carbon-carbon double bond to generate the ligand-degradable polymer, and the carbon-carbon double bond provides a lone pair of electrons required for the free radical reaction.
15. The medical device according to claim 14, characterized in that: The ligand containing a carbon-carbon double bond is selected from at least one of 2-amino-4-pentenoic acid, 2-acetamidoacrylic acid, maleic acid, fluocinol, allyl oxalate, octenylsuccinic acid, diethylenetriaminepentacarboxylic acid and maleic anhydride.
16. The medical device according to claim 1, characterized in that: The ligand is combined with the compound containing a carbon-carbon double bond and then reacts with the degradable polymer to obtain the ligand-degradable polymer.
17. The medical device according to claim 16, characterized in that: The ligand is selected from at least one of acids, esters, amides, amines, amino acids, peptides, and proteins, and the compound containing a carbon-carbon double bond is selected from at least one of vinyl isocyanate, ethylene acetic acid, vinyl acetate, vinyl sulfonic acid, versatate, vinyl sorbate, acrylic acid, methyl acrylate, and acrylamide.
18. The medical device according to claim 1, characterized in that: The ligand-degradable polymer is obtained by grafting a first reactive group onto a degradable polymer as a degradable polymer intermediate, and the degradable polymer intermediate reacts with a ligand containing a second reactive group. The first reactive group can react with the second reactive group, and at least one of the first reactive group and the second reactive group can release a coordination group.
19. The medical device according to claim 18, characterized in that One of the first reactive group and the second reactive group is selected from at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group, and the other is selected from at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group.
20. The medical device according to claim 19, characterized in that The ligand contains at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group. The degradable polymer is combined with a compound containing a carbon-carbon double bond to obtain a degradable polymer intermediate. The degradable polymer intermediate contains at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group. The ligand-degradable polymer is obtained by reacting the ligand with the degradable polymer intermediate.
21. The medical device according to claim 19, characterized in that The ligand contains at least one of an isocyanate group, a carboxyl group, an acyl chloride group and an epoxy group. The degradable polymer is combined with a compound containing a carbon-carbon double bond to obtain a degradable polymer intermediate. The degradable polymer intermediate contains at least one of an amino group, a hydroxyl group, a thiol group and a carboxyl group. The ligand-degradable polymer is obtained by reacting the ligand with the degradable polymer intermediate.
22. The medical device according to claim 1, characterized in that The medical device is loaded with an active drug.
23. The medical device according to claim 1, characterized in that The medical device is a vascular stent or a non-vascular intraluminal stent.
24. The medical device according to claim 1, characterized in that The medical device is an occluder.
25. The medical device according to claim 1, characterized in that The medical device is an orthopedic implant, a dental implant, a respiratory implant, a gynecological implant or an andrological implant.
26. The medical device according to claim 1, characterized in that The medical device is a suture.
27. The medical device according to claim 1, characterized in that The medical device is an orthopedic implant, and the orthopedic implant includes a fixing screw, a fixing rivet, a bolt or a bone plate.
28. The medical device according to claim 1, characterized in that The medical device is a non-vascular intraluminal stent, and the non-vascular intraluminal stent includes a tracheal stent, an esophageal stent, a urethral stent, an intestinal stent or a biliary stent.
